Tingkat Kematangan Gonad Bulu Babi (Tripneustes Gratilla) di Pantai Ahmad Rhangmayang Kecamatan Mesjid Raya Kabupaten Aceh Besar - Riza Nasrullah; Widya Sari; Siska Mellisa (Universitas Syiah Kuala, 2018)
This study aimed to determine the gonads maturity level of sea urchins (Tripneustes gratilla) found on Ahmad Rhangmanyang Beach, Mesjid Raya District, Aceh Besar Regency. Sampling was carried out from November to December of 2016 with a sampling interval of once a week. The location of the research sampling was done on Ahmad Rhangmanyang Beach, Desa Lamreh, Mesjid Raya District, Aceh Besar Regency (5°36'40.31